2013
DOI: 10.1016/j.jcf.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide decreases the bacterial load in a rat model of Pseudomonas aeruginosa pneumonia

Abstract: Gaseous nitric oxide (NO) is bactericidal in vitro. However whether and how it can be used for the treatment of bacterial lung infections in patients with cystic fibrosis is unclear. Here we assessed the bactericidal effect of intermittently inhaled 160 ppm NO for 30 min every 4 h in a Pseudomonas aeruginosa pneumonia model in rats. NO significantly reduced P. aeruginosa colony count in rat lungs but did not affect neutrophil myeloperoxidase function methemoglobin percentage nor plasma nitrite/nitrate levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 16 publications
3
38
0
4
Order By: Relevance
“…This initial in vivo study did not indicate an anti-inflammatory effect using gNO. In a previous study regarding bacterial pneumonia that was induced by P. aeruginosa, no influence of NO treatment was observed on the inflammation parameters, which was consistent with the present results (9). By contrast, the authors identified a marked reduction in the bacterial load of pseudomonades.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This initial in vivo study did not indicate an anti-inflammatory effect using gNO. In a previous study regarding bacterial pneumonia that was induced by P. aeruginosa, no influence of NO treatment was observed on the inflammation parameters, which was consistent with the present results (9). By contrast, the authors identified a marked reduction in the bacterial load of pseudomonades.…”
Section: Discussionsupporting
confidence: 93%
“…The present study hypothesized that i) bacteria were killed and ii) corneal inflammation was reduced following gNO treatment. It might be a similar situation in our keratitis model as in the pneumonia model described in the study by Miller et al (9) where inflammation was not reduced in contrast to the bacterial load. The bacterial load was not determined in the present study, as bacterial load can only be determined in the whole globes, but not separately within the cornea alone, due to the small structure of the murine cornea.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The potential of intermittent exposure to high levels of NO gas has been assessed in animal trials using rats. NO was delivered at 160 ppm (~7 µM NO) for 30 min every 4 h to rats with P. aeruginosa airway infection, and the results showed that the NO treatment was able to reduce the infection by more than 2 log [98]. Exposure to NO gas at 500 ppm (~20 µM NO) for 60 s every 24-48 h of external wounds colonised by S. aureus led to faster wound healing by 30%, compared to controls [99].…”
Section: At Higher Levels No May Be Effective At Killing Biofilmsmentioning
confidence: 99%
“…Nitric oxide (NO), an endogenously produced free radical that can disperse (12,13) and eradicate (14,15) biofilms, holds particular promise as an alternative to current antibiotic treatments. Gaseous NO has been repeatedly used to eradicate P. aeruginosa infections in small-animal models with no apparent toxicity (16,17). Under aerobic environments, NO reacts with molecular oxygen, superoxide, and hydrogen peroxide to form highly reactive intermediates (peroxynitrite, nitrogen dioxide, and dinitrogen trioxide).…”
mentioning
confidence: 99%